The experiences of rural British Columbians accessing surgical and obstetrical care - Aria Jazdarehee; Anshu Parajulee; Jude Kornelsen (The Beryl Institute, 2021)
The attrition of small volume surgical and maternity services in rural Canada over the past three decades has made access to these services especially challenging for rural citizens. While many of these closures have occurred as consequences of regionalization, a strategy to regionally centralize healthcare services, many studies investigating outcomes of regionalization have focused on costs and medical endpoints rather than the direct experiences of the rural patients affected. In this study, we aimed to understand and document the experiences of rural residents accessing procedural and maternity care both locally and away from home. This study is part of a larger evaluation framework which prioritizes the insight of rural residents regarding healthcare issues. We conducted focus groups and interviews with 54 participants in six communities across British Columbia's southeastern and northern regions. Thematic analysis showed that rural residents experienced unique challenges when leaving their communities to access care. This included logistics of travel, poor coordination of care between multiple providers, and financial and psychosocial issues. Despite being mostly content with the medical care received, participants expressed needing more attention to their unique needs and preferences as patients leaving their home communities for care. Understanding these challenges facilitates the planning of healthcare services in a more equitable manner. Our findings suggest that we need increased patient-centered healthcare planning that aims to alleviate the financial and psychosocial strain on rural residents. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Policy%20%26%20Measurement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.